(untitled) (Research, Society and Development, 2024)
Introduction: Traumatic Brain Injury, defined as a traumatic injury involving the scalp, skull, meninges, vessels and/or brain, is among the most common types of trauma in emergency services worldwide. This traumatic injury has extradural hematoma as one of its main and most lethal complications. Objective: The work describes the medical approaches carried out in the case of a patient victim of being run over, presenting with acute post-traumatic extradural hematoma. Description: The case of an elderly man who reported pain in the left lower limb, loss of consciousness and expectoration of blood with bone fragments is described. The head tomography showed an acute left frontotemporoparietal extradural hematoma associated with a bone fracture, with mass effect and midline shift. As a result of these findings, the patient underwent a left frontotemporoparietal craniotomy to drain the EDH. In the following days, progressing satisfactorily, he was discharged from neurosurgery. Discussion: The risk factors and trauma mechanism were addressed in order to discuss the possible evolution and prognosis. The progression of the lesion was explored and evaluated through the clinical picture and tomography, which was essential for diagnosing the type of lesion, therapeutic definition and therapeutic monitoring of the case. Conclusion: TBI requires careful management due to the possibility of a rapid unfavorable evolution of its complications. This case report highlights that EDH is a serious traumatic process that requires a rapid diagnosis to better conduct the available clinical-surgical management.